An Information Study on the Marketing Department of the PCED Hostel - Alabastro, John; Galicia, Eric; Belarmino, Noel; Ong, Andrew Jayson (College of Engineering, 1991)
The Philippine Center for Economic Development HOSTEL (PCED HOSTEL) was founded back in May 25, 1981 when it was donated by the Japanese government to the under the School of Economics. The purpose of the HOSTEL then was to serve as a dormitory for PCED clients, students and employees. After two years, in June 1983, under Director Encarnacion, the School of Economics donated the PCED to the University of the Philippines System. The PCED HOSTEL was under the U.P. system but was not to be fully absorbed. The PCED HOSTEL received no subsidy from U.P. and still had to give up a percentage of its revenues to the U.P. system. This was done to appease mounting labor unrest. The Administrative Order #101 created a band of overseers to manage the HOSTEL. This order, passed by then U.P. president Angara, enabled the U.P. board of overseers to manage the PCED HOSTEL. The HOSTEL is made up of four departments and ten sections, all under the board of directors. It has 60 rooms where 15 are devoted to the CIDS (Center for Integrative Development Studies) which is directly connected to the U.P. president. It also boasts of 7 function rooms for banquets and such. It also has a waiter-serviced Faculty Dining Room, a self-service Guest Cafeteria, and a Patio for evening functions.